The voice that challenged a nation : Marian Anderson and the struggle for equal rights - Freedman, Russell (Clarion Books, 2004)
Tells the life story of singer Marian Anderson, describing her famous 1939 Lincoln Memorial performance and explaining how she helped end segregation in the American arts after being refused the right to perform at Washington's Constitution Hall because of the color of her skin.